2021
DOI: 10.1021/acsanm.1c00646
|View full text |Cite
|
Sign up to set email alerts
|

Copper Single-Atom-Covered Pt Nanoparticles for Selective Hydrogenation of Phenylacetylene

Abstract: The selective hydrogenation of alkynes to alkenes is very important for both industry and scientific investigation, and overhydrogenation of alkynes to alkanes is the biggest problem to be solved. Suppressing the catalytic hydrogenation of alkenes to alkanes and keeping the efficient conversion from alkynes to alkenes at the same time is a viable solution, but the slight difference in structure between alkynes and the corresponding alkenes causes great difficulty in realizing such a target. The Pt/C− Cu bimeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Therefore, selective hydrogenation (e.g., semi-hydrogenation) of phenylacetylene to styrene was employed before styrene polymerization. [3][4][5][6] However, undesired byproducts like alkanes are inevitably generated due to overhydrogenation. So, it is urgent to develop novel catalysts with both high selectivity and activity for semihydrogenation of phenylacetylene.…”
Section: A Magnetically Separable Pd Single-atom Catalyst For Efficie...mentioning
confidence: 99%
“…Therefore, selective hydrogenation (e.g., semi-hydrogenation) of phenylacetylene to styrene was employed before styrene polymerization. [3][4][5][6] However, undesired byproducts like alkanes are inevitably generated due to overhydrogenation. So, it is urgent to develop novel catalysts with both high selectivity and activity for semihydrogenation of phenylacetylene.…”
Section: A Magnetically Separable Pd Single-atom Catalyst For Efficie...mentioning
confidence: 99%
“…It is generally accepted that palladium catalysts are mostly used to achieve a high catalytic performance for this reaction. Yet, it is difficult to design platinum-based catalysts that have good catalytic performance due to their low selectivity and poor stability. , The biggest problem is that the overhydrogenation of phenylacetylene to phenylethane often occurs in the platinum catalyst due to the weak cooperation of the active sites and the support environment, thus resulting in the catalytic hydrogenation of styrene that cannot be effectively avoided. …”
Section: Introductionmentioning
confidence: 99%
“…Impressively, the TOF value increases after the CpCo- fragments bonding on Pt/SiO 2 and further increases with the CpCo- coverage. The highest TOF on 200CpCo-Pt/SiO 2 (17 964.0 h –1 ) is also higher than most reported Pt and Pd-based catalysts. In addition, the reusability of 200CpCo-Pt/SiO 2 was tested. It is found that the selectivity and conversion are nearly similar after the consecutive recycling runs (Figure S14c).…”
Section: Resultsmentioning
confidence: 92%